INFLUENCE OF GAS GAP ON EFFICIENCY OF COOLING AND MICROSTRUCTURE OF CASTINGS AT FOUNDING OF SILUMINS IN METAL WATER-COOLED MOULD - V. Ju. Stetsenko; A. I. Rivkin (Литьë и металлургия, 2010)
Increase by 30–40% the linear speed of solidification of ingot with diameter 100 mm, to produce the castings with eutectic modified microstructure.